Tanggung Jawab Negara dalam Pemenuhan Jaminan Sosial Persepektif Welfare State - Tareq Jati Pamungkas; Achmad Hariri (Faculty of Law Universitas Muhamadiyah Yogyakarta, 2022)
The welfare state is intended to provide social services for all its citizens, as well as possible. In the concept of a welfare state, a country provides assistance or social security with the aim of achieving prosperity and welfare for its population. This study aims to determine the implementation of state responsibilities in welfare. The problem studied in this research is how the form of state responsibility in the perspective of the welfare state and how the form of social security responsibility according to Law no. 24 of 2011 concerning BPJS in the perspective of the welfare state. This study uses a type of normative research method based on written regulations and literature study. The results of this study indicate that the responsibility given by the welfare state is in the form of social services. In an effort to be responsible for realizing a welfare state, it is to make social policies by providing basic protection and services for compulsory education, basic living needs, health care, and social protection to vulnerable groups.